CADD [ computer-aided drafting and design (The way we communicate, 1997)
For architects, engineers and designers of all sorts, pencils and drawing boards are swiftly becoming obsolete. This program profiles the field of computer-aided drafting and design, describing both the technology and its industrial applications. Real-world examples of projects involving engines, electrical circuitry and heating and air conditioning systems illustrate the accuracy and efficiency associated with CADD, while expert users explain the ins and outs of how they do what they do